Personal Competence Mahasiswa Komunikasi Penyiaran Islam (KPI) Terhadap Konten Dakwah di Youtube - Arifah Yenni Gustia; Intan Khaira Nabila; Azizah Fitrah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Personal Competence is the ability to use, utilize, produce, analyze, and communicate messages through the media. Personal Competence consists of technical skills, critical understanding, and social competence. This study aims to look at personal competence of Islamic Broadcasting Communication students at UIN Imam Bonjol towards da'wah content on Youtube. This study uses a descriptive qualitative method with the results of the study in the form of written words. Data collection techniques in the form of interviews and documentation. The results of the study show that (1) Technically speaking, Islamic Broadcasting Communication students already have skills in using Youtube media but they lack access to the available da'wah features. (2) At the Critical Understanding, Islamic Broadcasting Communication students are active in analyzing accounts on Youtube media and are able to assess which accounts are worthy of being imitated for life (3) At the Social Competence stage, Islamic Broadcasting Communication students themselves have not been moved to distribute da'wah through Youtube